Ultrafast Prototyping of Large-Area Stretchable Electronic Systems by Laser Ablation Technique for Controllable Robotic Arm Operations - Gandla, Srinivas; Chae, Hyeokju; Kwon, Hyuk Jun; Won, Yoochan; Park, Hyeonjun; Lee, Sangheum; Song, Jaewoo; Baek, Seungho; Hong, Young Dae; Kim, Donghan; Kim, Sunkook (IEEE Transactions on Industrial Electronics, 2022)
On-skin stretchable electronic devices that can acquire electrophysiological signals for controllable human-machine interactions are of considerable importance in wearable robotics applications. The straightforward, large-area fabrication of structurally stretchable electronic sensors processed by ultrafast laser ablation techniques provides great insights into low-cost wearable stretchable sensors. In this article, a patch-based large-area frame-type stretchable sensor array system that covers a large portion (∼20 cm wide) of the human arm-processed by a simple, ultrafast (<4 min), user-accessible, mask-independent laser ablation technique-is demonstrated with resolutions down to 50 μm and 100% yield. The Ecoflex_PDMS-PEIE patch-an enabling material of soft (low modulus, ∼50 kPa), reversible adhesion to the skin (∼3.3 kPa), high permeability for water loss (∼8 gm-2h-1), and high stretchability (>100%)-allows the sensor to conformally attach to the skin for long-term usage. The patch-based sensor exhibited robust electromechanical properties under significant mechanical loadings for 10 000 cycles, a promising characteristic for product commercialization. Moreover, the results suggest that the proposed method is suitable for the fabrication of diverse materials for stretchable electronic applications. We verified the application of electromyography signals with human motion determination to control the movements of the robotic hand.
Keywords: Electromechanical property; High permeability; Human machine interaction; Laser ablation technique; Mechanical loading; Product commercialization; Sensor array systems; Stretchable electronics; Elastomers; electromyography (EMG); electrophysiological (EP) sensor; human-machine interaction; laser ablation technique; robotic arm; stretchable electronics